Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Efektivitas Kerja Karyawan PT. Erza Nusa Indonesia Gresik - Nur Cahyadi (FIRM Journal of Management Studies, 2016)
Effectiveness of the work of employees is not less important than the role of a leader or also urgently needed in an organization in order to achieve the result of work effectively and efficiently. This study aims to find, test and analyze the effect of leadership and discipline to the effectiveness of employees of PT. Erza Nusa Indonesia Gresik. This research is explanatory research using a quantitative approach. Population and also sample in this study were all employees of PT. Erza Nusa Indonesia Gresik were 67 people. This study uses the leadership and discipline as an independent variable, while the effectiveness of the work as the dependent variable. Analysis of the data in this study using SPSS version 21. The samples used were all employees of PT. Erza Nusa Indonesia Gresik de Ngan number of 67 respondents using total sampling method. On testing partially (t test) got those two variables have a significant influence on the effectiveness of the work. Where the significance probability value leadership variable (X1) of less than 0.05 is for 0000 with a beta value (β) of 0701, as well as work discipline variables (X2) is less than 0.05 is equal to 0.031 with a beta value (β) of 0302. To test result analysis based on F test conducted showed that leadership and discipline simultaneously or together have a positive significant impact on the effectiveness of employees of PT. Erza Nusa Indonesia Gresik.